THEORETICAL AND PRACTICAL APPROACH TO CORPUS BASED ANALYSIS OF LANGUAGE DEVELOPMENT - Ataboev, Nozimjon Bobojon ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the article, the description of the progress of this branch of science to date and the role of corpus analysis methods in the research on the enrichment of the lexical layer of the language are clearly demonstrated.